2015
DOI: 10.1055/s-0035-1567917
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Mapping of Sensory Nerve Endings in the Human Triangular Fibrocartilage Complex

Abstract: Background The triangular fibrocartilage complex is the main stabilizer of the distal radioulnar joint. While static joint stability is constituted by osseous and ligamentous integrity, the dynamic aspects of joint stability chiefly concern proprioceptive control of the compressive and directional muscular forces acting on the joint. Therefore, an investigation of the pattern and types of sensory nerve endings gives more insight in dynamic distal radioulnar joint stability.Questions/purposes We aimed to (1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(38 citation statements)
references
References 5 publications
0
37
0
1
Order By: Relevance
“…With regard to general distribution of sensory nerve endings, free nerve endings were the predominant receptor type, which is in accordance with the literature. Studies investigating ankle ligaments (Rein et al ) and the triangular fibrocartilage complex (Rein et al ) also report free nerve endings as the predominant receptor. This indicates that nociception has great importance in forearm rotation, axial forearm loading and weight lifting, reacting to harmful inflammatory, mechanical or chemical stimuli.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…With regard to general distribution of sensory nerve endings, free nerve endings were the predominant receptor type, which is in accordance with the literature. Studies investigating ankle ligaments (Rein et al ) and the triangular fibrocartilage complex (Rein et al ) also report free nerve endings as the predominant receptor. This indicates that nociception has great importance in forearm rotation, axial forearm loading and weight lifting, reacting to harmful inflammatory, mechanical or chemical stimuli.…”
Section: Discussionmentioning
confidence: 98%
“…The innervation of periarticular structures is characterized by specific sensory nerve endings, which have been studied extensively in the wrist (Hagert et al ; Hagert et al ; Rein et al ), as well as in the finger joints (Chikenji et al ), elbow (Petrie et al ; Kholinne et al ; Kholinne et al ), and shoulder joints (Morisawa, ) of the upper extremity. Recent studies have shown that the combination of the immunohistochemical marker of S100 protein (S100), low‐affinity neurotrophin receptor p75 (p75) and protein gene product 9.5 (PGP 9.5) allows a precise differentiation of specific neural and perineural structures in sensory nerve endings (Hagert et al ; Rein et al ; Rein et al ). Immunofluorescence techniques allow simultaneous presentations of different entities (Lee et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The location and size of the nerve bundles were documented and any nerve endings present were classified (Rein et al. , ; Stecco et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, orthopaedic surgeons should cooperate and consult with physical therapists to better understand the nonoperative treatment options for TFCC such as immobilization or proprioception training [5]. We also need to better understand the pathologies and consequences of the ulnar-plus variance as well as degenerative and traumatic tears.…”
Section: How Do We Get There?mentioning
confidence: 99%